A science of mind : the quest for psychological reality - Du Preez, Wilhelmus Petrus (Academic Press, 1991)
This book explains the social factors that shape the nature of theory and research traditions in psychology. It presents a broad treatment of the construction of theory and knowledge in science and philosophy with particular emphasis on psychological thinking. Du Preez, emphasizing the "evolution of knowledge," discusses theory and research across behaviorism, psychoanalysis, phenomenology, cognitive psychology, and many other psychological areas, placing them in their socio-philosophical contexts